Oracle essentials : oracle 9i,oracle 8i, and oracle 8 - Greenwald, Rick; Stackwiak, Robert; Stern, Jonathan (Beijing : O'reilley, 2001)
Computer Science
Keywords: Oracle; Oracle architecture; Oracle9i; Oracle 8i